2012
DOI: 10.1371/annotation/cd6e2d3b-4888-4231-a13d-6ef6170b79d6
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Biodiversity of Indigenous Saccharomyces Populations from Old Wineries of South-Eastern Sicily (Italy): Preservation and Economic Potential

Abstract: In recent years, the preservation of biodiversity has become an important issue. Despite much public discussion, however, current practices in the food industry seldom take account of its potential economic importance: on the contrary, the introduction of industrialized agriculture practices over large areas has often resulted in a dramatic reduction in biodiversity. In this paper, we report on the remarkable degree of biodiversity in the wine yeast populations naturally present in a small area of Sicily (Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Consumer and market demand for wines containing lower ethanol has shaped research to develop and evaluate strategies to generate low-ethanol wines [27]. Numerous studies have reported lower ethanol yields when using non-Saccharomyces yeast [23,28]. Another alternative is to exploit the oxidative metabolism observed in some non-Saccharomyces species [29].…”
Section: Contribution Of Non-saccharomyces Yeast Reduction In the Ethmentioning
confidence: 99%
“…Consumer and market demand for wines containing lower ethanol has shaped research to develop and evaluate strategies to generate low-ethanol wines [27]. Numerous studies have reported lower ethanol yields when using non-Saccharomyces yeast [23,28]. Another alternative is to exploit the oxidative metabolism observed in some non-Saccharomyces species [29].…”
Section: Contribution Of Non-saccharomyces Yeast Reduction In the Ethmentioning
confidence: 99%
“…Nowadays, the wine fermentation practices widely include the use of commercial Saccharomyces cerevisiae starters to ensure the reproducibility of fermentations from year to year and contribute to the production of more balanced wines [1][2][3]. However, the oenological practice of inoculated fermentation has determined a certain reduction and flattening of sensory characteristics of the final product, as a consequence of the decrease of diversity in microbial populations involved in fermentation [4,5]. Another problem is that the same commercial starter cultures were used for producing different wines, determining a uniformity in the wine characteristics, but the real number of commercial yeast strains is lower than we think, as manufacturers of different brands often designate the same strain with different codes or names [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An obvious consequence of the yeast inoculation practice is the standardization of sensory characteristics resulting from the fermentation process, including in quality wines, at the expense of the originality of aromas that could be expressed from the same products by exploiting indigenous micro-organisms [1,6]. In recent years, the exploitation of indigenous yeasts is a current topic in winemaking [7][8][9][10][11]. This trend supports safeguarding of the diversity of local products, and has a noteworthy impact in trade, especially by those consumers seeking typical foods.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, for a certain style of wines, the use of the so-called "indigenous (or autochthonous) yeasts" is considered essential in providing for the valorization and preservation of the environmental microbial biodiversity [6]. Indeed, it has been suggested that the land from which the grapes are grown imparts a unique quality to the wine, especially when spontaneous fermentations are carried out [7,12]. Thus, the wineries that employ indigenous yeasts promote the enhancement of biodiversity and the territorial microbiological heritage.…”
Section: Introductionmentioning
confidence: 99%